Whole exome sequencing reveals a stop-gain mutation of PKD2 in an autosomal dominant polycystic kidney disease family complicated with aortic dissection - Wenwen Zhang; Qian Han; Zhao Liu; Wei Zhou; Qing Cao; Weimin Zhou (BMC, 2018)
Abstract Background Autosomal dominant polycystic kidney disease (ADPKD) is the most common inherited kidney disorder characterized by progressive cyst formation and expansion in the kidneys, which culminates in end-stage renal disease. Aortic dissection is a rare vascular complication of ADPKD and related literature is currently limited. Case presentation In this report, we described a patient with asymptomatic Stanford B aortic dissection. Further investigation revealed a positive family history of ADPKD and normal renal function. Whole exome sequencing identified a stop-gain mutation c.1774C > T, p.Arg592Ter in the PKD2 gene that segregated in the family. To our knowledge, this is the first report of ADPKD complicated with aortic dissection caused by PKD2 mutation. Conclusions The case illustrates the importance of aorta imaging and molecular diagnosis in ADPKD patients in order to achieve early recognition of the deadly vascular complication.